Combined influence of hydrogen bonds and π–π interactions on the assembly of five manganese coordination polymers with magnetic properties. Issue 12 (7th March 2017) - Ye, Run-Ping; Zhang, Xin; Qin, Ye-Yan; Yao, Yuan-Gen
Abstract : Presented here are five Mn II coordination polymers assembled from a versatile ligand with the help of different N-donor auxiliary ligands. Of particular interest is that the structures of the title compounds vary from 1D to 3D. Abstract : Five novel interesting Mn(ii ) coordination polymers, [Mn3 (IDPA)3 (DMA)(H2 O)2 ] n · n [(H2 O)(DMA)] (1 ), [Mn(IDPA)(2, 2′-bpy)(H2 O)] n ·2 n (H2 O) (2 ), [Mn(IDPA)(phen)(H2 O)] n (3 ), [Mn(IDPA)(bpa)1/2 (H2 O)2 ] n · n (H2 O) (4 ), and [Mn(IDPA)(4, 4′-bpy)1/2 ] n (5 ) [H2 IDPA = 5-(1-oxoisoindolin-2-yl) isophthalic acid, bpy = bipyridine, bpa = 1, 2-bis(4-pyridyl)ethane, phen = 1, 10-phenanthroline, DMA = N, N -dimethylacetamide], have been synthesized with different N-donor ligands under solvothermal conditions and structurally characterized. The crystal structures of1–5 illustrate that hydrogen bonds and π–π interactions play critical roles in the construction of the extended supramolecular architectures. Compound1 possesses a two-dimensional (2D) layer structure with a uninodal 4-connected sql tetragonal plane net. Compounds2–4 feature one-dimensional chain (1D) structures, which further extend to 2D supramolecular networks via intermolecular π–π interactions and hydrogen bonds. Compound5 exhibits a most remarkable and unique three-dimensional (3D) framework with a binodal (4, 5)-connected new topology with the Schläfli symbol of {4 2 ·5 2 ·6 2 }{4 2 ·5 3 ·6 4 ·7}. Interestingly, the carboxylic groups of H2 IDPA display six different types of coordination modes in1–5 and the steric bulk of H2 IDPA plays an important role in influencing the structures of its compounds. Compound1 containing triangular trinuclear (Mn1⋯Mn2⋯Mn3) units displays weak antiferromagnetic interactions in the system, whereas compounds2–5 show that the overall magnetic interactions among the Mn(ii ) ions are weakly ferromagnetic. Besides, the thermal stabilities and luminescence properties of1–5 have also been investigated and discussed in detail.